Increasing Student Learning Activities Through Model Application Problem Based Learning (PBL) Material on the History of Colonialism and Imperialism in Class XI Asteroid at SMA Negeri 2 Medan - Sitanggang, Indri Cornelia; Sumantri, Pulung; Aisyah, Sitti (Jurnal Akuntansi Hukum dan Edukasi, 2024)
This study seeks to detail how class XI Asteroids students at SMA Negeri 2 Medan were able to increase their learning activities by using the Problem Based Learning (PBL) paradigm to content related to the history of colonialism and imperialism. The classroom action research (PTK) approach is used in this study to address a range of issues that transpire inside the educational setting. The four steps of this PTK are preparation, execution, evaluation, and review. Increasing students' historical learning activities is the primary goal of this study, and these four steps repeat themselves in a cycle to achieve this goal. The study was place in July and August of 2024 at SMA N 2 Medan and included students from class XI ASTEROID. Each of the two cycles of this study included two sessions. The study shows that with each cycle, pupils get more engaged in learning about history. The average proportion of student learning activities, which was 48.91% in cycle I and 75.78% in cycle II, shows this growth. Based on these findings, it can be concluded that the research success indicator has been met, with an average proportion of student learning activity reaching or above 70%, during cycle II.